Towards a string realization of the Dark Dimension via T-folds - Guo-En Nian; Stefan Vandoren (Journal of High Energy Physics)
Abstract In this work, we explore the feasibility of realizing the Dark Dimension Scenario through T-fold compactifications on T 5 × S 1, where the base of the internal space S 1 naturally acts as the requisite mesoscopic extra dimension. Utilizing Scherk-Schwarz reduction from 5D to 4D, and applying duality twists from both elliptic and parabolic conjugacy classes of subgroups of the T-duality group associated with T 5, we stabilize the volume of T 5 and several other moduli. This approach generates a potential characterized by two runaway directions, one aligned with the Scherk-Schwarz radion. Further stabilization efforts yield a decreasing potential trajectory demanded by the Dark Dimension Scenario.